Insights into cortical oscillations arising from optogenetic studies - Sohal, Vikaas S. (2012)
Cortical oscillations in the theta (4-10 Hz) and gamma (30-100 Hz) frequency range have been hypothesized to play important roles in numerous cognitive processes and may be involved in psychiatric conditions including anxiety, schizophrenia, and autism. Here we will review background information about these oscillations and their possible roles in psychiatric illness. Then we will describe findings from recent studies that used optogenetic tools to demonstrate that (1) a particular class of inhibitory interneurons expressing the calcium binding protein parvalbumin plays a central role in gamma oscillations, (2) gamma oscillations can entrain rhythmic firing in pyramidal neurons, and (3) rhythmic firing at theta and gamma frequencies can enhance communication between neurons. Finally we will discuss how these findings may relate to the pathophysiology of psychiatric conditions, as well as questions for future studies.